(untitled) (Sebha University Conference Proceedings, 2024)
High solar irradiation and ambient temperatures in regions like Libya can significantly decrease the electrical output of solar cells. This study investigates the impact of water and nanofluid cooling on the performance of a novel hybrid photovoltaic (PV) panel prototype. The prototype incorporates a water-based cooling system utilizing a water and Al2O3-water nanofluid within a rectangular collector at the rear of the PV panel. A comparative analysis is conducted using this collector technique. The closed-loop, passive cooling system directly contacts the PV panel through its rear side with varying nanofluid concentrations. Results demonstrate significant improvements in thermal efficiency, with increases of 48 % observed at nanofluid concentrations of 5 % volume. Electrical efficiency rises to 12.7 % and overall efficiency and total efficiency also exhibit a notable rise, reaching 60 % and 79.2% respectively at nanofluid concentrations of 5 % volume. additional enhancement of efficiency before and after using nanofluid as coolant increases to 5.5 %. In this study, a new style collector design was developed in addition to the suction plate. Additionally, the cooling cycle in the flow duct is carried out continuously using the water and water + Al2O3 as coolant. Therefore, the performance of the parallel channel of the plate, excluding PV/T and intermediate metal, was evaluated numerically. 3D numerical simulation was performed using finite element modeling (FEM) based on ANSYS Fluent software. Thus, the performance of PV/T obtained by the numerical simulation method was verified by external research.